Integrating Border Regions : Connectivity and Competitiveness in South Asia - Cali, Massimiliano; Farole, Thomas; Kunaka, Charles; Wagle, Swarnim (World Bank Group, Washington, DC, 2014)
Deeper regional integration can be beneficial especially for regions along international borders. It can open up new markets on opposite sides of borders and give consumers wider access to cheaper goods. This paper uses data from five contiguous districts of India, Nepal, and Bangladesh in the northeast of the subcontinent to measure the degrees of trade complementarity between districts. The paper illustrates that the regions are underexploiting the potential of intraregional commerce. Price wedges of up to 90 percent in some important consumption products along with measures of complementarity between households' production and consumption suggest the potential for relatively large gains from deeper trade integration. Furthermore, an examination of a specific supply chain of tea highlights factors that help industries scale up, aided by institutions such as an organized auction and decent physical and legal infrastructure. However, districts alike in geography but located across international boundaries face different development prospects, suggesting that gains from reduced "thickness of borders" would not accrue automatically. Much rests on developing intrinsic industry competitiveness at home, including the reform of regulatory and business practices and infrastructural bottlenecks that prevent agglomeration of local economies.